2000
DOI: 10.1016/s0304-3959(99)00274-2
|View full text |Cite
|
Sign up to set email alerts
|

The cognitive and psychomotor effects of morphine in healthy subjects: a randomized controlled trial of repeated (four) oral doses of dextropropoxyphene, morphine, lorazepam and placebo

Abstract: Ten healthy subjects (four male) of mean age 31 years (range 25-40) took part in a randomized double-blind four-way crossover study to examine the cognitive and psychomotor effects of repeated oral doses of dextropropoxyphene and morphine. Four treatments were compared: dextropropoxyphene napsylate 100 mg, morphine sulphate 10 mg, lorazepam 0.5 mg and placebo. Four doses of each drug were given at 4-h intervals to each subject on four separate study days at least 1 week apart. Cognitive function was assessed u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
2
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 20 publications
3
50
2
1
Order By: Relevance
“…The RA and FM groups reported greater use of opioid medications compared with the MSK group. However, although a variety of medications, including opioids, are known to affect cognitive function, recent data have shown that attentional functioning is either not disrupted or improves in individuals, including chronic pain patients, following opioid consumption using both performance and electrophysiological measures (17)(18)(19)(20)(21)(22). In our study, patients who received opioid medications did not perform significantly differently from patients who did not receive opioids.…”
Section: Discussioncontrasting
confidence: 52%
“…The RA and FM groups reported greater use of opioid medications compared with the MSK group. However, although a variety of medications, including opioids, are known to affect cognitive function, recent data have shown that attentional functioning is either not disrupted or improves in individuals, including chronic pain patients, following opioid consumption using both performance and electrophysiological measures (17)(18)(19)(20)(21)(22). In our study, patients who received opioid medications did not perform significantly differently from patients who did not receive opioids.…”
Section: Discussioncontrasting
confidence: 52%
“…The classes of drugs which are prescribed for inducing sleep, reducing anxiety or reducing a histaminic response have well documented side effects including reduction in activity during wake [22,23] and impairment of mental ability and alertness in the acute phase following drug administration [28,29]. Drug-induced reduction in activity has been studied in 'spontaneous' activity [29] and there are some data to suggest that actigraphy is able to detect "hangover effects" [18,22,28,[30][31][32][33]. These studies, however, have employed different actigraphs and not the Actiwatch® (Cambridge Neurotechnology Ltd., UK) which has been used in this present study.…”
Section: Introductionmentioning
confidence: 99%
“…23 Impairment of cognitive and psychomotor testing appears to be more pronounced when an opioid is administered parenterally, 24,25 as opposed to orally. 20,21 Furthermore, opioid-related impairment appears to be dose-related, 22 but in general the magnitude of impairment is markedly less than that associated with lorazepam. 20,21 Again, caution must be exercised when extrapolating the findings of these studies to the cancer population, on the grounds that volunteers are healthy and in no pain.…”
Section: Prevalence and Pattern Of Cognitive Effects Associated With mentioning
confidence: 99%
“…The presence of pain has been suggested by some authors to moderate the potentially negative influence of opioids on alertness and cognition. 21 The presence of pain as an antagonist to the sedative opioid effects is tentatively analogous to the effect of pain on the respiratory depressant effects of opioids, in which opioid-associated respiratory depression emerges when the pain stimulus is removed. 46 -48 Prospective studies in cancer patients that specifically examined opioid-related cognitive dysfunction are summarized in Table 3.…”
Section: Prevalence and Pattern Of Cognitive Effects Associated With mentioning
confidence: 99%